Era Digital: Peran Mediasi Kepuasan Kerja Terhadap Kompensasi dan Kompetensi Digital Karyawan BSI Pontianak - Angelina, Deva; Azazi, Anwar; Marumpe, Dody Pratama; Daud, Ilzar; Irdhayanti, Efa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic banking in Indonesia is currently facing complex challenges, given its relatively early stage of development compared to conventional banks. Amid intense competition in the national banking industry, Islamic banks must compete not only in service but also in innovation, technology, and human resource quality. This study examines the influence of compensation and digital competence on employee performance at Bank Syariah Indonesia (BSI) Pontianak Branch, with job satisfaction as a mediating variable. A quantitative, causal explanatory research design was applied. Data were collected through an online survey involving 167 BSI Pontianak employees selected via purposive sampling. Responses were measured using a 5-point Likert scale. The data analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4. The findings show that compensation significantly affects employee performance, while digital competence does not. Furthermore, job satisfaction has a significant positive impact on employee performance and mediates the relationship between compensation and performance. However, job satisfaction does not mediate the relationship between digital competence and performance, as job satisfaction at Bank Syariah Indonesia tends to be more influenced by external factors. These results highlight the importance of compensation and job satisfaction in improving employee performance within the Islamic banking sector..